The SMaRt: Design, implementation, and experiment - Top, Ahmet; Güngör, Gökhan; Gökbulut, Muammer (Hibetullah KILIÇ, 2023)
Mobile robots, for teaching and research activities, have an important place in all education levels, from higher to primary education. They provide a malleable platform to meet research and teaching needs in various engineering and science fields, such as mechanics, electronics, software, biology, and psychology. However, their high cost and the difficulty of learning the user interface and programming tools prevent the widespread use of mobile robots. In this study, we develop an affordable, symmetric, modular, interactive, human-aware, autonomous, and four-wheel-driven mobile robot to boost the quality of education and research. The proposed mobile system is fully customizable with open hardware, software, and data to meet the unique demands and specifications of teaching and research. The developed mobile robot has been successfully operated for education and research purposes.
Keywords: Electrical Engineering (Other); Elektrik Mühendisliği (Diğer)